Buletin Peternakan : PENGARUH PENAMBAHAN KARAGINAN DENGAN LEVEL YANG BERBEDA TERHADAP KOMPOSISI KIMIA, KUALITAS FISIK, SENSORIS DAN MIKROSTRUKTUR SOSIS AYAM - Arif Ismanto, Deny Sumarna (Peternakan UGM, 2016)
Various microfloras residing in the human colon are significantly affected by dietary fiber. Shortage of dietary fiber in the human daily consumption contributes to gastrointestinal metabolic and cardiovascular disease. One source of dietary fiber is a type of various seaweeds. This research was conducted to determine the effect of carrageenan addition on restructured meat products quality (chemical, physical, sensory and microstructure).